Experimental endocarditis: prophylaxis of Candida albicans infections by 5-fluorocytosine in rabbits. - Demierre, G (1979)
The prevention of Candida endocarditis in the rabbit was easily accomplished with a single intramuscular injection of 75 mg of 5-FC (A predominantly fungistatic agent) per kg either 40 min before, or at the same time as, the intravenous challenge with Candida albicans. Renal infarcts were observed more often in rabbits with infected valvular vegetations than in control rabbits with sterile endocarditis. The prophylactic effect of 5-FC is greater in aortic vegetations than in the kidneys. This may be related to differences in the pathophysiology of infection and the pharmacokinetics of 5-FC in the two areas.